The Relationship Of Diet And Physical Activity to The Incidence Of Adolescent Obesity - Yellyta Ulsafitri Handayani (IKES Payung Negeri Pekanbaru, 2025)
The World Health Organization (WHO) defines obesity as being determined by measuring body mass index (BMI) by measuring height and weight. In Indonesia, based on 2018 data, the prevalence of overweight and obesity in adolescents reached 13.5% . In West Sumatra, the prevalence of obesity in the age range of 15-24 years is 582,068 people. Meanwhile, in the city of Bukittinggi, the prevalence of obesity in the population aged ≥ 15 years is 61,877 people. Objectives: The sample in this study is all level 1 and level 2 students of the D III Midwifery study program with a total of 40 respondents. Methods: The type of research to be used is correlation analysis with a cross sectional design approach. The sampling technique in this study is non-probability sampling, namely purposive sampling. The sample in this study is all level 1 and level 2 students of the D III Midwifery study program with a total of 40 respondents. This research was conducted at Mohammad Natsir University. The initial data collection and survey started from February to March and this research was carried out for 1 week (3-8 June 2025). Body Mass Index (BMI) measurement was carried out in the Nutrition laboratory. counterfeit drugs using the logistic regression test. Results: More than half (62.5%) of respondents had a normal BMI (not obese). More than half (52.5%) of respondents have a good diet. A small percentage (40%) of respondentsB had strenuous physical activity. There was an effect of diet on obesity in students of Mohammad Natsir Bukittinggi University with the result of p Value = 0.011 (p<0.05). There was an effect of physical activity on obesity in students of Mohammad Natsir Bukittinggi University with the result of p Value = 0.046 (p<0.05) Conclusion: Obesity in adolescents is a global health problem, as it causes significant cardiometabolic and biochemical changes in the body including hypertension, dysphmia, hyperinsulin and an increased risk of Polycystic Ovary Syndrome (PCOS) in girls. For this reason, it is necessary to promote healthy lifestyle behaviors to prevent obesity. In addition, it is a multidisciplinary form of intervention that combines nutrition, exercise and psychological support in a family-based approach in adolescents by comparing the intervention group with the control group